2023
DOI: 10.3390/antiox12030647
|View full text |Cite
|
Sign up to set email alerts
|

Role of Cystathionine β-Synthase and 3-Mercaptopyruvate Sulfurtransferase in the Regulation of Proliferation, Migration, and Bioenergetics of Murine Breast Cancer Cells

Abstract: Cystathionine β-synthase (CBS), CSE (cystathionine γ-lyase) and 3-mercaptopyruvate sulfurtransferase (3-MST) have emerged as three significant sources of hydrogen sulfide (H2S) in various forms of mammalian cancer. Here, we investigated the functional role of CBS’ and 3-MST’s catalytic activity in the murine breast cancer cell line EO771. The CBS/CSE inhibitor aminooxyacetic acid (AOAA) and the 3-MST inhibitor 2-[(4-hydroxy-6-methylpyrimidin-2-yl)sulfanyl]-1-(naphthalen-1-yl)ethan-1-one (HMPSNE) were used to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…However, gastric mucosal expression of CBS was downregulated by ATB-344. In fact, overexpression of CBS has been suggested to contribute to the pathogenesis of various pathologies [ 48 , 49 ]. This is in line with the study of Scheid et al, where inhaled H 2 S prevented ischemia-reperfusion injury of neuronal tissue but also downregulated CBS expression [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, gastric mucosal expression of CBS was downregulated by ATB-344. In fact, overexpression of CBS has been suggested to contribute to the pathogenesis of various pathologies [ 48 , 49 ]. This is in line with the study of Scheid et al, where inhaled H 2 S prevented ischemia-reperfusion injury of neuronal tissue but also downregulated CBS expression [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, there has been growing interest in the role of CBS and H 2 S in cancer development and progression. Studies have shown that the elevated activity of CBS plays a significant role in promoting tumor growth, invasiveness, and metastatic potential (Youness et al, 2020;Padmanabhan et al, 2021;Santos et al, 2023). Consequently, the targeted inhibition of CBS could emerge as a promising therapeutic approach for cancer intervention.…”
Section: Introductionmentioning
confidence: 99%
“…Given the key role of 3MST in fostering cancer cell survival and augmenting cancer cell growth and proliferation [ 2 , 17 , 25 , 31 ], investigating its expression level in BC tissues could widen our understanding for the role of H 2 S synthesizing enzymes in BC tumorigenesis. Here, we screened in clinical breast cancer specimen the 3MST expression levels.…”
Section: Introductionmentioning
confidence: 99%